Chapter 9 A Methodological Approach for Integrative Framing Analysis of Television News - Dan, Viorela (Taylor & Francis, 2018)
This chapter lays out a set of procedures to investigate visual and verbal frames in news packages with an integrated approach. It provides an updated literature review on how audiovisual analyses can be conducted, reveals strengths and weaknesses of existing approaches, and adapts this advice to the necessities of visual news framing analyses. With a focus on issue framing, researchers will be guided through all the stages of the process from data collection to data analysis. Practical questions will be addressed, such as those concerning the unit of analysis, the preparation of the material, and strategies for frame identification and analysis. The chapter provides specific advice about how the interplay between verbal and visual frames in a news package can be measured in quantitative studies. All steps will be exemplified using a news package. The step-by-step delineation of a methodological approach to integrative framing analysis proposed here aims to spur more integrative studies and, through this, enhance our understanding of how journalists and their editors frame issues.